Post sovereign constitution making : learning and legitimacy - Arato, Andrew (Oxford : Oxford University Press, 2016)
Combining historical comparison, constitutional theory, and political analysis, this volume links together theory and comparative analysis in order to orient actors engaged in constitution making processes all over the world.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 25, 2016).
Keywords: Constitutional law; Law